2015
DOI: 10.1016/j.resuscitation.2015.07.050
|View full text |Cite
|
Sign up to set email alerts
|

The effect of resuscitation in 100% oxygen on brain injury in a newborn rat model of severe hypoxic-ischaemic encephalopathy

Abstract: Resuscitation in 100% oxygen does not cause a deleterious effect on brain injury following a severe hypoxic-ischaemic insult in a rat model of hypoxia-ischaemia. Further work investigating the effects of resuscitation in 100% oxygen is warranted, especially for newborn infants with severe hypoxic-ischaemic encephalopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…This suggests that we can use these short-term markers to identify useful temperature comparisons for more in-depth future investigations into mechanism and outcome. As we previously found that the hippocampus is the area that is most sensitive to the neuroprotective effects of HT at P14 10 15 , we also employed hippocampal area loss and CA1 neuronal counts in order to ascertain any further temperature-dependent changes in the hippocampus at this early time point 62 63 . However, in order to truly investigate whether milder cooling provides equivalent neuroprotection, long-term improvements in neurobehavioural outcome should be demonstrated, and this will be a focus of future work.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that we can use these short-term markers to identify useful temperature comparisons for more in-depth future investigations into mechanism and outcome. As we previously found that the hippocampus is the area that is most sensitive to the neuroprotective effects of HT at P14 10 15 , we also employed hippocampal area loss and CA1 neuronal counts in order to ascertain any further temperature-dependent changes in the hippocampus at this early time point 62 63 . However, in order to truly investigate whether milder cooling provides equivalent neuroprotection, long-term improvements in neurobehavioural outcome should be demonstrated, and this will be a focus of future work.…”
Section: Discussionmentioning
confidence: 99%
“…Hippocampal area loss was analysed in the moderate model, as previously described 62 63 . Sections at the level of the hippocampi were scanned at a higher resolution (2400dpi), and two consecutive sections from each animal were analysed with ImageJ.…”
Section: Methodsmentioning
confidence: 99%
“…A meta-analysis of 2133 babies13 revealed a reduction in mortality for infants resuscitated in 21% versus 100% oxygen (relative risk (RR) 0.69, 95% CI 0.54 to 0.88) and a trend towards a reduction in HIE. In animal models of neonatal asphyxia, resuscitation with 21% versus 100% oxygen resulted in comparable or improved outcomes of death, neurobehavioural disability and cell death 14. In an asphyxiated lamb model, 100% versus 21% oxygen for resuscitation caused an increase in cerebral blood flow (this is counterintuitive as cerebral vasoconstriction is the typical response with oxygen) 15.…”
Section: Advances In the Management Of Hiementioning
confidence: 99%
“…In animal models of neonatal asphyxia, resuscitation with 21% versus 100% oxygen resulted in comparable or improved outcomes of death, neurobehavioural disability and cell death. 14 In an asphyxiated lamb model, 100% versus 21% oxygen for resuscitation caused an increase in cerebral blood flow (this is counterintuitive as cerebral vasoconstriction is the typical response with oxygen). 15 The hypoxic brain may have lost autoregulatory abilities and be 'pressure passive', increasing the risk of hyperoxia and flow mediated brain injury.…”
Section: Advances In the Management Of Hie Resuscitationmentioning
confidence: 99%
“…The evidence regarding resuscitation with 100% oxygen is conflicting. A recent study done by Smit et al failed to show statistical difference in cortical and hippocampal volume loss or in short-term neurological testing between immature rats resuscitated with either 21 or 100% oxygen following a modified Rice-Vannucci model of hypoxic-ischemic brain injury (50). Newborn piglets resuscitated with 100% O 2 improved restoration of mean arterial blood pressure with no difference in amino acid build up in cerebral striatum (glutamate, taurine, and alanine) when compared to those resuscitated with 21% O 2 (63).…”
Section: Preclinical Studiesmentioning
confidence: 96%